Answer:
Option d
Step-by-step explanation:
-5(8x)
= -5×8×x
= -40x
Answered by GAUTHMATH
Answer:
f(x) = (x - (-5))^2 + (-18)
Step-by-step explanation:
Given:
f(x) = x^2 + 10x + 7
Rewrite f(x) in vertex form
Solution:
f(x) = ax^2 + bx + c is a quadratic function.
The vertex form of f(x) is a(x - h)^2 + k, where (h, k) is the vertex.
=> f(x) = x^2 + 10x + 7
= x^2 + 10x + 25 - 18
= (x + 5)^ - 18
= (x - (-5))^2 + (-18)
=> f(x) can be rewritten in form of a(x - h)^2 + k, where (h, k) is the vertex, with a = 1, h = -5, k = -18
The number is 8 because 4 times 8 equals 24 plus 2 is 26
Answer:
Step-by-step explanation:
Recursive formula
tn = t_n-1 / 4
t2 = t1 / 4
t2 = 10240
t1 = 10240 / 4 = 2560
Explicit formula
tn = 10240 / 4^(n-1)
t4 = 10240 / 4^(4 - 1)
t4 = 10240 / 4^3
t4 = 10240 / 64
t4 = 160
t8 = 10240 / 4^7
t8 = 0,625